PENERAPAN METODE WEB BASED LEARNING SEBAGAI SOLUSI PENDIDIKAN YANG EFEKTIF DAN EFISIEN - Nasution, Taruna (Jurnal TIMES, 2015)
Learning, in practice it can't avoid technology purpose especially Information Technology (TI). Information technology have can give contribution for world education. Learning gets effective and efficient, interactive, far ranging, and unpatronised just in room brazes. This condition of make Information Technology make education quality that can be prided. Informations Technological purpose Internet in education the world gets to be realised by its benefit and current Technological Information Internet one that â€œ trend â€ deep learning is by applying method base learning's web , it was caused by that technology was evident can give contribution for studentâ€™s (student / college student and teacher / lecturer) in their learning activity. Examination is done by use of PHP software( Personal Home Page ),Â  macromedia dreamweaver, camtasia sudio, cool edits,Â  and photoshop's Adobe Â to get result as learning interactive gets basis content Â multimedia by methodics base learning's web Â one that is applied to college student.